2012
DOI: 10.1002/14651858.cd004418.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Empiric antibiotic coverage of atypical pathogens for community-acquired pneumonia in hospitalized adults

Abstract: No benefit of survival or clinical efficacy was shown with empirical atypical coverage in hospitalized patients with CAP. This conclusion relates mostly to the comparison of quinolone monotherapy to beta-lactams. Further trials, comparing beta-lactam monotherapy to the same combined with a macrolide, should be performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
7

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 68 publications
3
61
0
7
Order By: Relevance
“…Eliakim-Raz et al showed no benefit of survival or clinical efficacy of atypical coverage in hospitalized patients with CAP, except for patients with Legionella infection, but this conclusion was mostly related to the comparison of fluoroquinolone monotherapy to beta-lactams (6). Similarly, Mills et al showed no advantage of antibiotics active against atypical pathogens over BL antibiotics in nonsevere CAP, again with the exception of patients with Legionella pneumonia (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eliakim-Raz et al showed no benefit of survival or clinical efficacy of atypical coverage in hospitalized patients with CAP, except for patients with Legionella infection, but this conclusion was mostly related to the comparison of fluoroquinolone monotherapy to beta-lactams (6). Similarly, Mills et al showed no advantage of antibiotics active against atypical pathogens over BL antibiotics in nonsevere CAP, again with the exception of patients with Legionella pneumonia (16).…”
Section: Discussionmentioning
confidence: 99%
“…However, this benefit was not observed in patients who received guideline-concordant antibiotics (6). In another meta-analysis that included studies in critically ill patients with CAP only, macrolide use was associated with a significant 18% relative reduction in mortality compared to nonmacrolide therapies (8).…”
Section: Discussionmentioning
confidence: 99%
“…Otras guías recomiendan Iniciar dentro de las primeras 8 horas posteriores al diagnóstico. (Nivel de evidencia II -Grado de recomendación B) (23,25,26,27,28,29,30,31,51).…”
Section: ¿Qué Medidas Son Fundamentales En El Tratamiento?unclassified
“…These recommendations are somewhat at odds with those provided by the British Thoracic Society in 2009, which recommend oral amoxicillin monotherapy for low-severity CAP 3 . A 2012 Cochrane Review on the subject investigated the utility of adding atypical coverage to empiric therapies and found no benefit 11 . Furthermore, the authors of that study were unable to find a quality randomized controlled trial (RCT) comparing β-lactam monotherapy to said therapy plus a macrolide and emphasized the need for such a study.…”
Section: Literature Reviewmentioning
confidence: 99%